Juridical Review of Sundanese Traditional Marriage and Its Recognition in National Law - Afnaini, Afnaini; Hamdan, Hamdan (LEGAL BRIEF, 2024)
Sundanese traditional marriage is a tradition rich with cultural values and local wisdom that has been carried out for generations by the Sundanese people. This research aims to review juridically the implementation of Sundanese traditional marriages and their recognition in the Indonesian national legal system. The research method used is a normative juridical method with a statutory approach and a case approach. Data was obtained through literature study and analysis of relevant legal documents. The research results show that although traditional Sundanese marriages are carried out in accordance with local traditions and cultural norms, there is an urgent need to ensure official registration of marriages at the Civil Registry Office. This registration is important to legally recognize marriage and protect children's rights, especially in terms of birth certificates and division of inheritance. Without official registration, children born from traditional Sundanese marriages can face challenges in claiming their legal rights, including inheritance rights and administrative protection. Integration between customary law and national law is necessary to ensure that all aspects of marriage are legally recognized and protected, avoiding potential discrimination and conflict in the future